2015
DOI: 10.1007/s11368-015-1196-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying sources of suspended sediment in three size fractions

Abstract: Purpose Identifying of the sources, stores and pathways of sediments in a catchment is essential to accurately target management actions designed to reduce sediment delivery to receiving waters. Fingerprinting the source of sediment using geochemical properties has increasingly been accepted as an accurate approach for quantifying the contribution of different sources to river sediment discharge. In this study, we seek to examine the effect of particle size and location of the sources on their contribution to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…In a nested watershed with distint geological materials, Haddadchi et al () observed proximal sources tended to contribute more to a given river sampling point than more distal sources. Minella et al () observed that the budget calculations indicate that rural small watershed had a sediment delivery ratio of ∼15%, whereas in our watershed study, a sediment delivery ratio was only 0.71% (Rodrigues, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a nested watershed with distint geological materials, Haddadchi et al () observed proximal sources tended to contribute more to a given river sampling point than more distal sources. Minella et al () observed that the budget calculations indicate that rural small watershed had a sediment delivery ratio of ∼15%, whereas in our watershed study, a sediment delivery ratio was only 0.71% (Rodrigues, ).…”
Section: Discussionmentioning
confidence: 99%
“…forests on water and land resources are not well known, and there are uncertainties about the ability of production land to support planted forests without degrading those natural (Reichert et al, ; Rodrigues et al, ). Sediment in suspension and bedload sediment cause environmental problems (Bilotta & Brazier, ; Haddadchi, Olley, & Pietsch, ; Owens et al, ). Sediment sources identification contributes to maintaining natural resources quality in forest production systems, the management of resources, and the establishment of proper use and management techniques to limit or reduce degradation, especially on the watershed scale.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this difference seems minor, it was significant and likely mitigated by the 71 particulate matter samples. In comparison, Haddadchi et al (2015) reported that there was an absolute mean difference of 14% (SD 8%) between the <10 mm and the 10e63 mm and 13% (SD 9%) between the <10 mm and the 63e212 mm fraction. The larger mean differences and standard deviations reported by these authors likely relates to the fact that they compared isolated fraction ranges, they used elemental geochemistry which is inherently more complex, and they modelled only 8 sediment samples for comparison.…”
Section: Particle Sizementioning
confidence: 94%